A Chemotherapy Responsive Ewing Sarcoma Case Report With a Rare FUS::FLI1 Fusion - Ismail M. Elbaz Younes; G. Thomas Budd; Yu-Wei Cheng (Case Reports in Pathology)
Ewing sarcoma is a rare but aggressive type of cancer, primarily occurring in teenagers and young adults, characterized by having a small round cell morphology with positive diffuse membranous CD99 immunostaining of these small round blue cells. Although this cancer is often found in bones, it can also extend into the soft tissue in some cases. A gene fusion of one of the FET family RNA-binding proteins, including EWSR1 and FUS genes as 5′ partners, and one of the ETS family transcription factors as 3′ partners, is the defining genetic characteristic of essentially all Ewing sarcoma cases. We report a case of a 42-year-old male individual with retroperitoneal Ewing sarcoma who underwent chemotherapy treatment following the biopsy diagnosis that revealed the FUS::FLI1 fusion. To the knowledge of the authors, this is the first report of response to chemotherapy in a case of Ewing sarcoma showing a rare FUS::FLI1 fusion.